The effect of exercise on level of general health of pregnant women - Sadeghi, azam; Sirati-nir, masood; Hajiamini, zahra; Ebadi, abas; Naderi, zeinab; Mehdizade, soodabeh (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim: Prenatal care is one of the most confident and basic services to protect fetomaternal health. This study aimed to evaluate the effect of physical exercise on level of general health of pregnant women. Materials and Methods: This was a quasi-experimental clinical trial study. The research samples included 60 primigravid women referred to the prenatal-care clinic of Baghiatallah hospital in Tehran. The participants were randomly divided to two experimental and control groups. The experimental group was trained for 1.5-2 hours in groups with 3 to 4 members and then they began to practice. No training was performed for control group. Level of general health of two groups was investigated by general health questionnaire (GHQ-28), before and 8 weeks after the intervention. Data were analyzed by analytic and descriptive statistical testes. Findings: Sixty primigravid women with average age of 26/77 years and average gestational age of 8/13 weeks participated in the study. The education level of majority of participants was highschool diploma and they have no history of exercise during pregnancy. Before intervention, the total scores for GHQ were 38/06 and 29/46 in experimental and control groups, respectively. After intervention, the total scores were 19/2 and 27/5 in experimental and control groups, respectively. T test showed a significant difference between two groups his before and after the intervention (p<0/05). The mean scores for all dimension of general health showed significant difference between two groups of study (p<0/05). Conclusion: Results showed the positive effects of physical exercises on physical and psychosocial dimension of general health of pregnant women. Keywords: Pregnant women, Physical exercise, General health Corresponding Author: Azam Sadeghi, Master of Science in Nursing, Akhtar Hospital, Shahid Beheshti University of Medical Sciences, Tehran,Iran Email: a.sadeghi29151@yahoo. REFERENCES -Barakat R Pelaez M Montejo R et al (2011). Exercise during pregnancy improves maternal health perception: A randomized controlled trial. American Journal of Obstetrics and Gynecology. 204 (5) 402. E1-7. -Dabiran S Hatmi ZN (2005). [New approach to exercise in pregnancy].Journal of Tehran University of Medical Science. 63 (12) 974-979. (Persian) -Dumas G Reid J Wolf L Griffin M et al (1995). Exercise, posture and back pain during pregnancy. Clinical Biomechanics. 10 (2) 98-103. -Ebrahimi A Molavi H Moosavi G et al (2007). Psychometric properties and factor structure of general health questionnaire 28 (GHQ-28) in Iranian psychiatric patients.Journal of Research in Behavioral Sciences. 5 (1) 5-11 (Persian) -Gibbons P Arevalo H Mnico M (2004). Assessing of the factor structure and reliability of the 28 item version of the General Health Questionnaire (GHQ-28) in El Salvador. International Journal of Clinical Health Psychology. 4(2) 389- 398 -Goodwin A Astbury J McMeeken J (2000). Body image and psychological well-being in pregnancy. A comparison of exercisers and non-exercisers.The University of Melbourne, Victoria, The .Australian & New Zealand Journal of Obstetrics Gynaecology.40 (4) 442-7. -Kazemi A Ahmadi P (2007). [Correlation of physical activity in first 20 week of pregnancy and preeclampsia]. Journal of Shahrecord University of Medical Science. 9 (2) 20-27 (Persian) -Larsson S lord Lindquist PG (2005). Low impact exercise during pregnancy, a study of safety. ACTA Obstetricia et Gynecologica Scandinavica, 84 (1) 34-38 > 15/ ... F#> G - 00 9 ! - B> -Leiferman J Evenson K (2003). The effect of regular leisure physical activity on birth outcomes. Maternal & Child Health Journal. 7 (1) 59-64 -Masoodzade A Khalilian A Ashrafi M et al (2002). Survey of status of psychology health of students of Sari high school. Journal of Mazandaran University of Medical Science. 14 (45) 74-82 (Persian). -Melzer K Schutz Y Boulvain M et al. (2010). Physical activity and pregnancy: cardiovascular adaptations, recommendations and pregnancy outcomes. 40 (6) 493-507. -Memari A Ramimi T Amini M et al (2006). The effect of aerobic exercise on pregnancy and outcome. Hayat.12 (3) 35- 41 (Persian). -Moslemi Haghighi F Kazemi B (2000). [The relationship of low back pain with gravida and delivery]. Journal Qazvin University of Medical Science. 4 (3) 46-51. (Persian) -Motahhari Tabari N Mirdar Sh Khaledan A et al (2010). [The effect of Aerobic Exercise on pregnancy outcome]. Journal of Babol University of Medical Science. 12 (1) 36-43 (Persian) -Sedaghati P Arjmand A Sedaghati N (2006). [Does regular ergometric training have any effect on pregnancy outcome?] Iranian Journal of Pediatrics. 16 (3) 325-331(Persian) -Sedaghati P (2004). [Influence of a period of regular physical exercise on anxiety of pregnant women in second and third trimester in Qom]. Master Thesis of physical education. Faculty of Humanities, Tarbiat Modarres University (Persian) -Sehatie Shafai F Sadeghi khamene S Kushavar H et al (2006). [Lifestyle and its correlation with outcomes of pregnancy in pregnant women referred to educational hospitals of Tabriz]. Nursing and Midwifery Journal of Tabriz. 1 (3) 28-32 (Persian) -Shivakumar G Brandon AR, Snell PG et al (2011). Antenatal depression: a rationale for studying exercise. Depression and anxaeity. 28 (3) 234-42. -Sorensen T Williams M Lee I et al (2005). Recreational physical activity during pregnancy and risk of preeclampsia. Hypertension. 41(6) 1273-80 -Stora (2007). [Tension or stress: New Disease of Civilization], Translated by Dadsetan P, 2 nd edition, Tehran, Roshd Publication. 179-186 (Persian) -Zand S Zamani A (2009). [The effect of simple exercise maneuvers and proper performance of daily activity on outcome of pregnancy]. Journal of Obstetrics Gynecology and Infertility of Iran. 12(3).51-57. (Persian)